Meningkatkan Hasil Belajar (pada Materi Aku Memiliki Kemampuan ) Bagi Peserta Didik Kelas VII-2 SMP Negeri 1 Nainggolan - Rianita Lumban Tobing; Alfonsus Mudi Aran; Aserie M.M.Dungus (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of Grade VII-2 students on the topic "I Have Abilities" through the application of the Problem-Based Learning (PBL) model for students at SMP Negeri 1 Nainggolan in the 2024/2025 academic year. The PBL method was chosen for its ability to enhance student engagement, critical thinking skills, and problem-solving abilities relevant to everyday life. This research employs a classroom action research (CAR) design involving two cycles of action. Data were collected through learning outcome tests, observations of the learning process, and evaluation questionnaires. The results of the study show a significant improvement in students' learning outcomes, as evidenced by increased test scores and positive feedback from students regarding the learning process. The implementation of the PBL model also demonstrated improvements in students' collaboration skills and learning motivation. Therefore, the use of the Problem-Based Learning model can be considered effective in improving students' learning outcomes in the taught material.